2017
DOI: 10.4172/2375-4494.1000357
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder (PTSD) in Sexually Abused Children and Educational Status in Kenya: A Longitudinal Study

Abstract: Children who experience sexual abuse often meet the criteria of Post-Traumatic Stress Disorder and other psychiatric disorders. This article examines Post-Traumatic Stress Disorder and their educational status among children who have been sexually abused and its effects on the children’s educational status. The study was carried out between June 2015 and July 2016. The study adopted a longitudinal study design. The study was conducted at Kenyatta National Teaching and Referral Hospital and Nairobi Women’s Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…A longitudinal study conducted in Kenya among 191 children age 7-17 years who had experienced sexual abuse found that at baseline the prevalence of full PTSD was 95.3% [33]. This finding could have been higher than this study because the research was done in the biggest referral hospital in Kenya.…”
Section: Discussioncontrasting
confidence: 63%
“…A longitudinal study conducted in Kenya among 191 children age 7-17 years who had experienced sexual abuse found that at baseline the prevalence of full PTSD was 95.3% [33]. This finding could have been higher than this study because the research was done in the biggest referral hospital in Kenya.…”
Section: Discussioncontrasting
confidence: 63%
“…This paper was part of a Kenyan longitudinal study on the psychosocial outcomes associated with sexual abuse among children aged 7–17 years who were treated at the Kenyatta National Hospital (KNH), the National Teaching and Referral Hospital. The study was also conducted at a specialised private Gender-Based Violence (GBV) hospital, the Nairobi Women’s Hospital in Nairobi, Kenya [ 18 ]. The two are the leading and specialized hospitals in (GBV) in Kenya, based in Nairobi City.…”
Section: Methodsmentioning
confidence: 99%
“…After a child had been randomly selected to participate in this study after 1-month exposure to the sexual abuse incidence, the parents/legal guardians were approached to give informed consent to participate in this study and assent from the children. The children were put on the standard prophylactic and therapeutic treatments regimes, usually provided at the GBVR centres in both hospitals [ 18 ]. This included Post exposure Prophylaxis (PeP) against HIV and contraceptive prophylaxis (CP), treatment of physical injuries and psychosocial care in the hospitals and or referred to legal services providers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the time of the initial assessment, only Mouilso et al [23] prospectively assessed participants prior to the sexual assault. The other nine assessed participants at various time-frames post assault -within one week (Herbert et al [21]), 12 days (Rothbaum et al [27]), two weeks (Oshodi et al [26]), four weeks (Darves-Barnoz et al [18], Mutavi et al, 2017 [24], Mutavi et al, 2018 (majority of participants within one month) [25]), six weeks (Elklit et al [19], Khadr et al [22]) or within a variable timeframe (46% of the sample within 8-10 weeks post-assault (Feiring et al [20]).…”
Section: Baseline Characteristicsmentioning
confidence: 99%